Design and Development of Bi-layered Sustained Release Azithromycin Tablets (Dhaka University Journal of Pharmaceutical Sciences, 2017)
The objective of the current study was to develop a bilayer tablet of Azithromycin containing both immediate and sustained layer and evaluate the effect of formulation variables on drug release. Thirty different formulations (F-1 to F-30) were prepared by direct compression. When the fraction of polymer was increased from 5.55% to 10%, the rate of drug release was found to be slower. Maximum release of Azithromycin was from F-11 (within 8 hours), which contained 50 mg (5.55%) of HPMC 50 cps. Slowest release was observed from F-30 containing 90 mg (10%) of Carbopol 974 P. The IR spectral analysis revealed that all rate regarding agents and excipients used in this study are compatible with the active Azithromycin.Dhaka Univ. J. Pharm. Sci. 15(2): 227-234, 2016 (December)